271 Frequency of neonatal lupus in reference centers in the management of pregnancy and autoimmune diseases. (April 2019) - Maldini, Carla; Otaduy, Cintia; Mollerach, Florencia Beatriz; Scolnik, Marina; Virasoro, Belen Maria; Pisoni, Cecilia; Croce, Mercedes; Hu, Maria; Camargo Serrudo, Fabiola Natalia; Dubinsky, Diana; Leon, María de la Paz; Bellomio, Veronica; et al.
Abstract : Background: Neonatal lupus (NL) is a disease in children of mothers who have specific anti-Ro/La IgG autoantibodies by passive transplacental transfer. LN is characterized by skin and cardiac involvement, as well as cytopenias, hepatic or neurological manifestations. NL can be diagnosed intra-uterus or in neonatal period, being self-limiting in several months or be irreversible. Congenital heart block (CHB) in a structurally normal heart, is perhaps the most serious manifestation with an estimated mortality rate of around 19%. Objetives: to estimate the frequency of NL in children of mothers with anti-Ro/La in reference centers in the management of pregnancy and autoimmune diseases in Argentina, and to describe maternal and children features. Methods: A descriptive multicenter study was conducted in reference centers in the management of autoimmune diseases and pregnancy in Argentina. Inclusion criteria were the presence of positive maternal serology anti-Ro/La and at least one pregnancy. Demographic and maternal-fetal clinical data were obtained from the clinical histories and each center completed a data collection form created for this study. We defined a NL case (born or not) who presented, pre and/or postpartum, characteristic skin lesions, cytopenias, cardiac involvement (CHB, endocardial fibroelastosis and dilated cardiomyopathy), hepatic or neurological manifestations. Ethnicity was classified using GLADEL groups. NL frequency was calculated dividing the number NL cases by the number of mothers with positive anti-Ro/La serology. Results: 18 reference centers in the management of autoimmune diseases and pregnancy participated in this study in 7 different geographic areas of Argentina (6 of Buenos Aires, 6 of Cordoba, 1 of Jujuy, 1 of Mendoza, 1 of Santa Fe, 1 of Santiago del Estero and 2 of Tucuman). 193 mothers with positive anti-Ro/La serology were included with 364 pregnancies. 19 cases NL cases were reported (10 diagnosed during pregnancy and 9 in post-partum. The frequency of NL was estimated at 9.8% [95% CI 6.3–14.9] (CHB=6.2% [IC95% 3.5–10.7]). Table 1 describes the maternal and fetal characteristics of NL cases. The most frequent manifestations were skin (n=7) and cardiac involvement (n=12). In 1 case, there was a history of NL in a previous pregnancy. Of the patients with CHB, 5 required a pacemaker. Conclusions: In conclusion, the frequency of NL in our multicentric cohort is greater than other international cohorts. Differences could be related to genetic/environmental factors as well as methodological limitations and selection bias. Funding Source(s): None